Memecylon edule leaf extract mediated green synthesis of silver and gold nanoparticles - Elavazhagan T (Dove Medical Press, 2011)
Tamizhamudu Elavazhagan, Kantha D ArunachalamCentre for Interdisciplinary Research, Directorate of Research, SRM University, Kattankulathur-603203, Tamilnadu, IndiaAbstract: We used an aqueous leaf extract of Memecylon edule (Melastomataceae) to synthesize silver and gold nanoparticles. To our knowledge, this is the first report where M. edule leaf broth was found to be a suitable plant source for the green synthesis of silver and gold nanoparticles. On treatment of aqueous solutions of silver nitrate and chloroauric acid with M. edule leaf extract, stable silver and gold nanoparticles were rapidly formed. The gold nanoparticles were characterized by UV-visible spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDAX) and Fourier transform infra-red spectroscopy (FTIR). The kinetics of reduction of aqueous silver and gold ions during reaction with the M. edule leaf broth were easily analyzed by UV-visible spectroscopy. SEM analysis showed that aqueous gold ions, when exposed to M. edule leaf broth, were reduced and resulted in the biosynthesis of gold nanoparticles in the size range 20–50 nm. TEM analysis of gold nanoparticles showed formation of triangular, circular, and hexagonal shapes in the size range 10–45 nm. The resulting silver nanoparticles were predominantly square with uniform size range 50–90 nm. EDAX results confirmed the presence of triangular nanoparticles in the adsorption peak of 2.30 keV. Further FTIR analysis was also done to identify the functional groups in silver and gold nanoparticles. The characterized nanoparticles of M. edule have potential for various medical and industrial applications. Saponin presence in aqueous extract of M. edule is responsible for the mass production of silver and gold nanoparticles.Keywords: Memecylon edule, nanoparticles, bioreduction, electron microscopy, FTIR